Do Capital Incentives Distort Technology Diffusion? Evidence on Cloud, Big Data and AI - Timothy DeStefano; Nick Johnstone; Richard Kneller; Jonathan Timmis (CESifo GmbH, 2024)
The arrival of cloud computing provides firms a new way to access digital technologies as digital services. Yet, capital incentive policies present in every OECD country are still targeted towards investments in information technology (IT) capital. If cloud services are partial substitutes for IT investments, the presence of capital incentive policies may unintentionally discourage the adoption of cloud and technologies that rely on the cloud, such as artificial intelligence (AI) and big data analytics. This paper exploits a tax incentive in the UK for capital investment as a quasi-natural experiment to examine the impact on firm adoption of cloud computing, big data analytics and AI. The empirical results find that the policy increased investment in IT capital as would be expected; but it slowed firm adoption of cloud, big data and AI. Matched employer-employee data shows that the policy also led firms to reduce their demand for workers that perform data analytics, but not other types of workers.
Keywords: J21; J24; L20; O33; 330; capital incentives; firms; cloud computing; artificial intelligence